No need for Rody son, in-law to testify - Palace - Salaverria, Leila B. (Philippine Daily Inquirer, 2017)
President Duterte's son and son-in-law need not testify in a Senate investigation of the smuggling of "shabu" and corruption in the Bureau of Customs after key informant, Mark Taguba, cleared them of involvement.